Habitual constipation in children as a challenge in the physiotherapist's practice - Katarzyna Strojek (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Stool constipation, according to the opinion of GPs, pediatrics and pediatric gastroenterology specialists, is one of the most common ailments among the youngest patients. The incidence of constipation varies and depends on many factors, mainly environmental, sociological and economic ones. It also depends on the gender and age of the child. It is estimated that up to 10% of the developmental age population suffers from chronic constipation. The above-mentioned ailment is most common in children from 2 to 4 years old and is slightly more common in boys than in girls. In 90-95% of cases, constipation develops on an idiopathic functional basis [1-4]. Habitual constipation in children is a very serious clinical problem because it prevents the patient from proper functioning, and thus contributes to a reduction in life quality and lowers self-esteem. In the international literature, issues related to physiotherapeutic treatment of habitual constipation appear quite rarely. Nowadays, there has been a significant increase in the interest in improving the quality of life in the youngest patients. An attempt to treat functional constipation in children should be made at the level of primary care, including comprehensive treatment and physiotherapy.